Study the Effect pf Using Intensifying Screen on Magnitude of Changing Calibration Curve For Dental X-Ray Film in Manual evelopment Method - Qusay KH O Al-Dulamey; Muna Y Shamon; Hanaa N Akrawy (University of Mosul, College of Dentistry, 2008)
Aim: To study the effect of using intensifying screen (Rare Earth ),with a film which dose not exist with it. Materials and Methods: The patient received the radiation dose during dental fustigation by x-ray radiation. The optical density of the x-ray film was measured using densitometer. Result: A decrease in radiation dose was approximately 20% for the same condition . 241Am was used, because its energy (59.5keV) is close to the energy of x-ray in dental radiography. Conclusions: It is essential to use intensifying screen I.S in the diagnoses field of dentistry for the purpose of reducing the amount of radiation dose. It could be concluded that small calibration operation must be determined during the regular interval periods for the optical density measurements of the optical density by densitometer to show its efficiency